Case report: Epigastric heteropagus twins and literature review - Zhu, Wenbin; Cui, Xiongjian; Wu, Zhaohan; Li, Zhaolin; Chen, Gang; Liang, Suixin; Mao, Jianxiong (Frontiers in Pediatrics, 2023)
Epigastric heteropagus twins are an extremely rare congenital anomaly of conjoined twins. We present a case of epigastric heteropagus twins who were diagnosed via prenatal ultrasound imaging: the fetus (or host) was connected to the abdominal wall of the parasite (the dependent portion), and an omphalocele was present. The male infant was delivered by cesarean section at 35+5 weeks gestation. The parasite lacked a head and heart and presented long bones of the limbs. After abdominal computed tomography, omphalocele repair and parasite removal were surgically performed under general anesthesia. After discharge (follow-up, 3 months), the infant is currently growing well and is healing satisfactorily. Forty-one cases of epigastric heteropagus twins were retrieved from database searches: 38 good postoperative outcomes, 2 perioperative deaths, and 1 termination. The case highlights that even when parasites are massive in size, births can present good outcomes with suitable surgical treatment.